Desenvolvimento da energia eólica no Ceará, no Brasil e no mundo: uma solução energética viável - Gomes, Rafael de Moura (2016)
This study aims to present succinctly and update data related to wind power generation in the world, Brazil and Ceará. The wind power continues to play a leading role among the alternative sources, due to increasingly lower costs in recent years, reaching $ 14 per MW. In Brazil, the Plano Decenal de Expansão da Energia is expected to arrive in 2023, with 11.4% of participation in the national energy matrix, totaling 22.4 GW. In Ceará, it is estimated that in the coming years, the energy matrix will have 50% of energy from wind farms. The lack of natural resources for the operation of other electrical sources, along with the wind potential of the state, has transformed the energy matrix of Ceará and proportionate economic development to the region.